Quantitative ocean-column acoustic imaging over the Calypso Hydrothermal Vent Field, Bay of Plenty: first results from R.V. Tangaroa TAN1806-QUOI Voyage - Lamarche, G; Ladroit, Y; Le Gonidec, Y; Lucieer, V; Weber, T; Gaillot, A; Gerring, P; Heffron, E; Lassalle, C; Mitchel, G; Nau, A; Pallentin, A; et al. (., 2018)
The aim of the TAN1806-QUOI (Quantitative Ocean-Column Imaging using hydroacoustics) voyage on RV Tangaroa was to improved methods to characterise bubbles in the water column originating from seafloor targets such as cold gas seeps and hydrothermal vents. The July 2018 20-day voyage focused on the Calypso Hydrothermal Vent Field (CHVF), ca. 15 km SW of Whakaari-White Island volcano which is well known for such seafloor features. Six complex experiments were designed (1) Calibration and cross calibration of two multibeam and six split-beam echosounders systems (SBES) providing 38, 70, 120, and 200 kHz frequencies; (2) multibeam surveys with 75% and 95% swath footprint overlap on natural seeps and bubbles generated using a synthetic seep generator (aka bubble maker), allowing us to model the angular response of seafloor and water-column backscatter, and sidelobe interference; (3) a multi-angle survey over synthetic and natural bubbles using a hull-mounted pan&tilt device; (4) an horizontally looking SBES for lateral observation of bubble streams; (5) a 5 days passive acoustic recording at the northern CHVF; (6) video footage, sediment and water samples for signal validation.p> The different frequencies shows strikingly different acoustic responses demonstrating the potential of multi-frequency and wideband data for analysis of gas bubbles. Correlating acoustic frequency responses with physical parameters (depth, temperature, salinity) will enables us to estimate bubble-size distributions and flux rates (rising speed). When coupled with video observations and water sample analysis, these methodologies enhance our ability to model gas flux for discrete areas of seafloor. Preliminary results show potential for the development of automated methods to extract estimates from water column acoustic data in real time. The survey demonstrated that acoustic means can be used to differentiate spatially coincident gas bubbles (here methane and CO 2 ). Such methods could be applied to other targets such as freshwater streams.